The Squirting Donuts - Adler, David A. (Naperville, Illinois : Sourcebooks Jabberwocky, an imprint of Sourcebooks, Inc., 2014)
Danny and Calvin decide to find out why their fourth-grade teacher, Mrs. Cakel, is suddenly behaving very strangely by not only failing to enforce her many rules, but by violating some herself.
Keywords: Eccentrics and eccentricities -- Juvenile fiction; Intellect -- Juvenile fiction; Friendship in children -- Juvenile fiction; Teachers -- Juvenile fiction; Schools -- Juvenile fiction; Eccentrics and eccentricities -- Fiction; Intellect. -- Fiction; Friendship -- Fiction; Teachers -- Fiction; Schools -- Fiction; Mystery and detective stories